1984
DOI: 10.1007/bf00021129
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of allozyme variants and linkage groups in lentil

Abstract: The genetics of 8 electrophoretically detectable enzymes in lentil was examined . The enzyme systems glutamic-oxaloacetic transaminase, malic enzyme, phosphoglucomutase, alcohol dehydrogenase, 6-phosphogluconate dehydrogenase, shikimic dehydrogenase and isocitrate dehydrogenase were assayed . The allozymes at each of the studied loci behaved in a codominant manner and segregated in the expected Mendelian fashion . Linkage tests between these loci and an additional morphological trait revealed two linkage group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 8 publications
(4 reference statements)
4
48
0
1
Order By: Relevance
“…These linkages are likely orthologous to the tepary bean linkage between Gpi-c2 (and by extension Adh-T) and Aat-2. In lentil, these loci were found to be separated by 21 cM (Zamir and Ladizinsky 1984), as was the case in tepary bean. In chickpea, the loci Fdh and Gpi< are separated by 7 cM (Gaur and Slinkard 1990).…”
Section: Locus Pairmentioning
confidence: 60%
See 1 more Smart Citation
“…These linkages are likely orthologous to the tepary bean linkage between Gpi-c2 (and by extension Adh-T) and Aat-2. In lentil, these loci were found to be separated by 21 cM (Zamir and Ladizinsky 1984), as was the case in tepary bean. In chickpea, the loci Fdh and Gpi< are separated by 7 cM (Gaur and Slinkard 1990).…”
Section: Locus Pairmentioning
confidence: 60%
“…Several of the isozyme linkages in tepary bean appear to be conserved in other legume genera as well. For instance, linkage between Got-3 and Adh has been detected in lentil (Zamir and Ladizinsky 1984), and in pea Aat-c and Adh-1 are known to be on the same linkage group ). These linkages are likely orthologous to the tepary bean linkage between Gpi-c2 (and by extension Adh-T) and Aat-2.…”
Section: Locus Pairmentioning
confidence: 99%
“…Phylogeny and genetic diversity of the genus Lens has been studied first by seed protein electrophoresis (Ladizinsky, 1979b;Sultana et al, 2006) and isozyme markers (Zamir and Ladizinsky, 1984;Pinkas et al, 1985;Hoffman et al, 1986;Muehlbauer et al, 1989;Erskine and Muehlbauer, 1991;Mayer and Soltis, 1994;Ferguson and Robertson, 1996). The DNA-based markers, such as RFLP (Havey and Muehlbauer, 1989;Muench et al, 1991;Rajora and Mahon, 1994), RAPD (Sharma et al, 1995;Ferguson et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009;Tewari et al, 2012), AFLP (Sharma et al, 1996;Zavodna et al, 2000;Duran and Perez de le Vega, 2004;Kahraman et al, 2004;Rubeena et al, 2006;Fiocchetti et al, 2009;Toklu et al, 2009), microsatellite markers (Duran and Perez de le Hamwieh et al, 2009;Liu et al, 2008;Babayeva et al, 2009;Reddy et al, 2010;Gupta et al, 2012, Tewari et al, 2012Zaccardelli et al, 2012), inter simple sequence repeat (ISSR) (Zavodna et al, 2000;Sonnante and Pignone, 2001;Toklu et al, 2009), internal transcribed spacers (ITS) (Fernandez et al, 2000;Mayer and Bagga, 2002;…”
Section: Genus Lens Millermentioning
confidence: 99%
“…Skibinski et al 9 identified allozymic variation at an aspartate aminotransferase locus which they designated Aat-1. Zamir and Ladizinsky 19 described the inheritance of eight allozyme polymorphisms and the presence of two linkage groups. In one of these linkage groups, the gene for green epicotyl, Gs, was placed 14 map units from Got-2 (Aat-1 of Skibinski et al 9 ) and 25 map units from a gene coding an isozyme of malic enzyme, Me-1.…”
mentioning
confidence: 99%